Directrices para el desarrollo económico, cultural y social de Pamplona, Colombia - Orlando Edmundo Jaimes Flórez; Jemay Mosquera Téllez (Mundo Fesc)
This research highlights the importance of understanding the basic concepts of economic, social, and cultural development, which could lead to the progress of any territory through proposals generated by government officials and developed jointly with communities. The study employs a mixed methodology, presenting a systematic integration of quantitative and qualitative methods, with a deductive and cross-sectional approach. The methodological phases address the importance of social, cultural, and economic development from the perspective of the potential for achieving internal development in each country and recognizing the importance of culture within communities; analyze the role of culture in the socioeconomic development of Pamplona, ​​Norte de Santander; and propose guidelines for the articulation of economic, social, and cultural development as a tool for transforming and appropriating the municipal territory through different spaces for youth participation and leveraging technological advances, social networks, and globalization through these mass media. The results can be very useful for municipalities with significant cultural heritage or for contexts that wish to promote economic development through cultural management.